Hemangioma of the Rib Mimicking Chondrosarcoma: A Report of Two Cases and Literature Review. (28th September 2021) - Tsuda, Yusuke; Kobayashi, Hiroshi; Makise, Naohiro; Zhang, Liuzhe; Shinoda, Yusuke; Ushiku, Tetsuo; Tanaka, Sakae
Abstract : Cases . Case 1 was a 58-year-old man who presented with an incidentally detected, slowly growing mass in the right hypochondrium area. An imaging study showed the mass arising from the 11th rib, with ill-defined margins and cortical destruction. Differential diagnoses included chondrosarcoma and metastatic malignant tumor. Open biopsy was associated with moderate bleeding (300 mL) despite small incision. Microscopic findings showed numerous irregular, dilated, and thin-walled vessels, consistent with the diagnosis of hemangioma of bone, and en bloc excision was performed with no surgical complication. Case 2 was a 49-year-old man who presented with an incidentally detected 4th rib mass with calcification on computed tomography scan. Chondrosarcoma was suspected according to imaging features. An open biopsy was considered to have a risk of tumor seeding because the tumor was located behind the scapula. En bloc excision of the tumor without biopsy was performed. The pathological findings were consistent with hemangioma of bone. Conclusion . We reported two cases of rare hemangioma arising from the rib, which mimicked chondrosarcoma. The preoperative diagnosis was challenging, both clinically and radiologically. Because biopsy for hemangioma of the rib is associated with a bleeding risk, the en bloc excision without biopsy can be a practical treatment option.